ROLE OF THE SEROLOGIC TEST FOR DENGUE VIRUS INFECTION - Ni Luh Sinta Purnama Dewi; I.A Putri Wirawati (E-Jurnal Medika Udayana, 2013)
Dengue virus infection is infection disease cause by dengue virus. Dengue virus infection can cause a broad spectrum disease such as : dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS). Currently dengue virus ranks eighth as a cause of illness in the State of South-East Asia and Western Pacific. Epidemic dengue hemorrhagic fever (DHF) occur each year in Indonesia with a tendency incident and the affected area is increasing. Laboratory tests can be done to detect the dengue virus infection: a complete blood count and serology. Of serology test, positive IgM antibody showed that patients had a primary infection, whereas patients with secondary infections showed positive IgG antibodies, usually accompanied by antibody IgM positive.